2006
DOI: 10.1159/000097077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Hemodialysis Session on bcl-2 Expression in Peripheral Blood Mononuclear Cells in vivo

Abstract: bcl-2 is a proto-oncogene with a regulatory role in many conditions due to its marked inhibitory action on apoptosis. Reports regarding the effect of hemodialysis (HD) on apoptosis of mononuclear cells and in association with bcl-2 expression in particular, are controversial. The aim of the present study was to examine in vivo the influence of an HD session on bcl-2 expression of lymphocytes and monocytes. We measured quantitative bcl-2 expression with flow cytometry, in terms of antibodies bound per cell, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Existing data suggest that enhanced apoptosis appears in the progression of CKD and uremic milieu per se is partly responsible for the phenomenon [1,2,3,9,10]. We demonstrated that expression of Bcl-2 decreased significantly in the course of CKD which remained the only independent predictor.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Existing data suggest that enhanced apoptosis appears in the progression of CKD and uremic milieu per se is partly responsible for the phenomenon [1,2,3,9,10]. We demonstrated that expression of Bcl-2 decreased significantly in the course of CKD which remained the only independent predictor.…”
Section: Discussionmentioning
confidence: 51%
“…Increased apoptosis of leukocytes has been described in hemodialysis (HD) and non-dialysis patients, while miscellaneous factors, such as, uremia, acidosis, oxidative stress, iron overload and malnutrition have been implicated [1,2,3]. In addition, a significant percentage of HD patients demonstrate an activated inflammatory response in the absence of any apparent cause [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, interpretation of pre-post studies has to be done carefully. This holds also true for a study that did not find differences in expression of the proto-oncogene bcl-2 in monocytes [108]. Since the expression increased in lymphocytes (thus indicating inflammatory activation) the lack of effect on monocytes might be caused by sequestration of the activated cells from the circulation.…”
Section: The Role Of Hemodialysis Treatment On Monocytes Phenotype and Functionmentioning
confidence: 79%
“…hand, the report in this issue of Blood Purification by Koliousi et al [5] evaluated the effect of a hemodialysis (HD) session using two different types of membrane (cellulosic and synthetic) on in vivo bcl-2 expression of lymphocytes and monocytes. bcl-2 expression increased significantly in lymphocytes after the HD procedure, irrespective of the membrane used.…”
Section: Is Bcl-2 a Key Molecule In The Abnormalmentioning
confidence: 99%